Geo-Politics in Northeast Asia - Iwashita, Akihiro; Ha, Yong-Chool; Boyle, Edward (Politics in Asia, 2023)
Geo-Politics in Northeast Asia focuses on the dynamics of Northeast Asia as a region. The chapters in this book offer a nuanced approach for understanding the geo-politics of this strategically critical area of the world. Focusing on China, Japan, Russia, and the Koreas, as well as the involvement of the United States, the contributors to the volume offer a timely and critical analysis of Northeast Asia. They collectively emphasize the different scales at which the region holds significance, and particularly note how the region is often granted significance by local political forces as well as national interests. Borderlands and sub-regions are especially important in this perspective, and the contributors show both how regionalism influences the people living in these areas and how they in turn shape the political priorities of states. At the same time, the worsening of relations between Japan and the Koreas and the increasing assertiveness of both China and Russia make it essential to understand the dynamics of the region, as well as how they have changed during and following the Trump era. Geo-Politics in Northeast Asia is essential reading for students and scholars of Political Geography, International Relations and Strategic Studies, as well as for those with a research focus on Northeast Asia, or the wider Asia-Pacific and Indo-Pacific regions.